2006
DOI: 10.1556/abiol.57.2006.1.7
|View full text |Cite
|
Sign up to set email alerts
|

The genotoxic effects of logran onHordeum vulgareL. andTriticum aestivumL.

Abstract: In the present study, the cytogenetic effects of the herbicide Logran on root tip cells of Triticurn aestivum L. and Hordeum vulgare L. and changes of total protein content in root tip meristems were studied. The seeds of plants were treated with various concentrations of Logran (125, 250, 500 microg/ml) for 3 and 6 h. The percentages of abnormal cells were seen to increase with increasing treatment period and concentrations. The most dominant types of observed abnormalities were C-mitosis, distributed metapha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…This observation confirmed other data that T. аestivum is appropriate test object in toxicity assays [37,38].…”
Section: Methodssupporting
confidence: 92%
“…This observation confirmed other data that T. аestivum is appropriate test object in toxicity assays [37,38].…”
Section: Methodssupporting
confidence: 92%
“…The confirmation of macroscopic effects by microscopic events is in accordance with statement of other authors (Aybeke et al, 2008;Kaymak and Muranli, 2006) that T. aestivum is a suitable test plant for toxicity testing.…”
Section: Allium Cepa-testsupporting
confidence: 89%
“…For toxicity test, seeds of T. aestivum were used. T. аestivum is proved to be appropriate test object in toxicity assays [30] [31]. Results of our previous study (data not shown) revealed that A. vernalis at concentration used in traditional medicine (hot extract, 6.67 g/l) inhibited the root growth of T. аestivum seeds by 78.31% in comparison to untreated control.…”
Section: Root Growth Inhibition Test and Determination Of Effective Cmentioning
confidence: 99%